An error analysis on EFL students' writing - Mubarok, Yasir; Budiono, Taat (Englisia Journal, 2022)
This study attempts to analyze the grammatical errors in the writings of Indonesian EFL students through the Error Analysis (EA) approach. The subject of this research included the theses which are written by the university students of English Letters Department at one of the State University, Jakarta. The data sources were taken from chapter four, the conclusion, and the suggestion section from six students’ theses. In this study, the data collection was carried out through several steps: the authors collected data from students, identified grammatical errors, classified errors in students' thesis to determine the frequency of errors, and calculated the data into percentages. The results indicate that there are eleven types of errors commonly found in students’ writing. They are 5% errors of subject-verb and agreement, 2% errors in word order, 13% errors in preposition, 20% errors in article, 2% errors in plurality form, 19% errors in punctuation, 5% errors in auxiliary, 21% errors in unnecessary words, 5% errors in word choice, 5% errors in parallel structure, and 2% errors in redundancy. The writer observed 125 total errors. The errors are dominated in the form of punctuation, article, and unnecessary words types. The research unveils that students make common grammatical errors encouraged by the incapability to accomplish, recognize and understand the rules of the foreign language and its limitations, a little mastery of grammar and vocabulary.